Diagnosis and spread of dermatomycosis among small breed dogs in Ternopil - Chupryna, M.; Ivanchenko, I.; Severyn, R. (Scientific Progress & Innovations, 2022)
More than 85 % of skin diseases of infectious origin in dogs are caused by fungal infections. The main causative agents are dermatophytes. Sick animals not only pose an epizootic hazard but also affect the health of their owners. the significant epidemiological threat is not animals clinically suffering from dermatophytoses, but asymptomatic carriers. Among them, it is the companion animals that often become the cause of human infection. Despite the fact that for humans there is a significant number of "own" pathogens of fungal diseases – anthropophiles (Epidermophyton flocossum, T. rubrum, T. tonsurans, T. mentagrophytes var. interdigitale, M. audouinii), they are more often affected by zoophilic fungi (M. canis, T. verrucosum, T. mentagrophytes var. gipseum), which imposes a special responsibility on veterinarians. Individually or in associative forms, they cause allergic conditions, skin, cerebral, corneal, or decimated mycoses in humans. The research was conducted in 2022 in the conditions of a private veterinary clinic in the city of Ternopil. The research materials were dogs of small breeds (Yorkshire terriers, Maltese, bichons, spitz) with signs of dermatoses, as well as biomaterials from them (skin scrapings, smears – impressions on polymer film), which were studied in the clinic's own laboratory. Sixty-four dogs were examined, including 28 with a positive result. The culture method on the DSM Dermakit selective medium and the direct microscopy method were used to identify pathogens. On the basis of the conducted studies, it was established that the share of fungal diseases among dermal pathologies in small breed dogs in the city of Ternopil was 43.7 %. In addition to the traditional causative agents of dermatophytosis (T. mentagrophytes, T. rubrum, M. canis, M. gypseum), opportunistic fungi were revealed, which were previously considered contaminating microflora (Malassezia, Alternaria). Pathogens caused the disease both independently and in associated forms (53.6 % and 46.4 %, respectively). It is worth mentioning that representatives of the genus Alternaria caused independent diseases in 35.7 % of cases. Pathogens of the genus Malassezia were detected only in associated forms (28.6 %). Applying the cultural diagnostic method based on the DSM Dermakit selective medium, it was possible to quickly and conveniently identify animal mycosis patients among dogs with signs of dermatopathology. The most important means for making a final diagnosis was a direct microscopy when examining both scrapings from affected areas of the skin and fragments of colonies after their growth on DSM media.